Knowledge, attitude, and practice of physicians regarding pain management in patients with Sickle cell disease - Ismail, Abdellatif; Aqel, Ali; Abumuhfouz, Ma’in; Safieh, Mohamad; Arabyat, Mahmoud; Ibrahim, Mohamed; Singh, Kalpana; Yassin, Mohamed A. (Frontiers in Hematology, 2023)
Sickle cell disease (SCD) is a hemoglobin disorder inherited in an autosomal recessive pattern. Pain from vaso-occlusive crises (VOCs) is the most common symptom experienced by patients with SCD; thus, pain management constitutes a significant role in this patient population. We hypothesized that physicians with less favorable attitudes toward SCD patients are less likely to follow pain management guidelines. In this cross-sectional convenience sample survey, we aimed to assess the adherence of physicians in our institute to guidelines for the management of SCD pain crises and study the factors that are associated with non-adherence to these guidelines. Most surveyed physicians were early in their career and were found to adhere to the recommendations of using opioids and NSAIDs as a first-line therapy and avoiding using meperidine. On the other hand, some analgesic practices deviated from the recommendations, including less frequent assessment and reassessment of pain and response to pain medications and less frequent use of opioid patient-controlled analgesia (PCA). It is noteworthy that the frequency and severity of untreated pain in patients with SCD are associated with higher mortality, thus appropriate comprehensive care for such a vulnerable population should be prioritized and optimized. Although we did not find an association between the providers’ attitudes toward SCD patients and their pain management practices, improving these attitudes will promote the provider–patient relationship and its therapeutic outcomes. We conclude that the physicians taking care of SCD patients in our institute adhere to some of the guidelines in the field more than others. We also conclude that they have negative attitudes toward SCD patients; nevertheless, these did not affect their pain management practices.